Effects of Blended Poly(3-hexylthiophene) and 6,13-bis(triisopropylsilylethynyl) pentacene Organic Semiconductors on the Photoresponse Characteristics of Thin-Film Transistors - Shin, Hyunji; Lee, Hyeonju; Kim, Bokyung; Zhang, Xue; Bae, Jin-Hyuk; Park, Jaehoon (Korean Journal of Metals and Materials, 2022)
In this study, we demonstrate high-performance optical wavelength-selective organic thin-film transistors (TFTs) that incorporate heterogeneous organic semiconductor materials, poly(3-hexylthiophene) (P3HT) and 6,13-bis(triisopropylsilylethynyl) pentacene (TIPS-pentacene). The electrical characteristics of the fabricated transistors were analyzed in the dark to determine how the P3HT:TIPS-pentacene ratio of the semiconductor affected the performance of the transistor. Specifically, the P3HT:TIPS-pentacene weight ratio was varied (1:0, 1:0.25, 1:0.5, 1:0.75, 1:1, and 0:1) by blending 1 wt% P3HT dissolved in chloroform, and 1 wt% TIPS-pentacene dissolved in anisole. The UV-visible light absorbance characteristics of the films containing the P3HT, TIPS-pentacene, and P3HT:TIPS-pentacene blends were analyzed. Monochromatic light at wavelengths of 515 and 450 nm was used to clarify the influence of irradiation on the electrical characteristics of the TFTs. The results confirmed that the TFT containing P3HT:TIPS-pentacene at a blending ratio of 1:0.5 had the largest light-to-dark current ratio, i.e., approximately 33.8 and 23.5 when exposed to monochromatic light at wavelengths of 515 nm and 450 nm, respectively. The TFT with the P3HT:TIPS-pentacene blending ratio of 1:0.5 exhibited the highest photosensitivity values of 261.9 and 49.6 upon irradiation with light at wavelengths of 515 nm and 450 nm, respectively. The observed improvement in the performance of the heterogeneously blended organic transistors is discussed in relation to the morphological structure and charge transport path of the P3HT:TIPS-pentacene blended semiconductor films.